Study of Mycoplasma and Ureaplasma Species as Contaminats of Cell Cultures - 1MH Salari; R Hafezi; H Khosravipoor (Tehran University of Medical Sciences, 2002)
Mycoplasma and Ureaplasma species are the most serious contaminants of cell cultures and this remains one of the major problem encountered in biological research using cell cultures. The aim of this study was to investigate the rate of Mycoplasma and A total of 100 different cell culture specimens including, R228, Hela, Vero, MDCK, L20, RD and Hep2 were collected. Then the specimens were investigated by culture method and biochemical tests. The rate of contaminant cell culture specimens was 32%. The highest and lowest rate of contamination was observed among Hela cell culture (25%) and R238 cell culture (0%), respectively. Moreover, the results of χ2 statistical analysis test, showed significant difference between contamination rate and kind of cell culture ( p = 0/001). It is concluded that Mycoplasma and Ureaplasma species are the most common source of further contamination of cell cultures.